Blended Synchronous Learning and Students’ Critical Thinking Ability: Lesson from Covid-19 - Bagus Shandy Narmaditya; Putra Hilmi Prayitno; Sheerad Sahid; Agus Wibowo; Yuli Agustina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
The Covid-19 pandemic has been a primary issue, and the educational sector has responded to this issue by providing various alternative learning activities to provide the indifference essence as in the normal situation. In more specific, this study aims to examine the implementation of blended synchronous learning-based and its impact on students’ critical thinking in economics. This study applied mixed methods, quasi-experimentally by using non-equivalent control group design research to determine the different changes during the experimental period. The findings of the study indicate that in addition to diminishing tedium in the classroom, blended synchronous learning outraces the conventional learning and can explain an increase in critical thinking abilities of students. Additionally, this study demonstrates the remarkable different between treated students and control group in the term of critical thinking from the perspective of SOLO taxonomy.Keywords—blended synchronous learning, critical thinking ability, blended learning, learning management system